Representasi Matematis Siswa dalam Menyelesaikan Soal Cerita Perbandingan Senilai Ditinjau dari Jenis Kelamin - Martina, Martina; Lefrida, Rita; Alfisyahra, Alfisyahra; Pathuddin, Pathuddin (Jurnal Pendidikan Matematika : Judika Education, 2024)
This study aims to obtain a description of the mathematical representation of grade VIII students of SMPN Model Terpadu Madani in solving comparative story problems in terms of gender. This type of research is qualitative research with a qualitative descriptive approach. The subjects of the study were 2 students of SMPN Model Terpadu Madani, namely 1 male student and 1 female student. Data collection techniques used in this study include written tests and interviews. The results of the study showed that male and female students used indicators of mathematical representation, namely verbal representation, symbolic representation, and visual representation when solving comparative story problems. The verbal representation of male and female students was able to write down the steps to solve mathematical problems according to the indicators. The symbolic representation used by male and female students was able to write equations, mathematical models, mathematical operations and solve problems involving mathematical expressions. The conclusion is that male and female students generally use visual representation, but there are differences between male and female students. Male students only use pictures to clarify while female students use pictures and tables to clarify and facilitate problem solving. Keywords: Mathematical Representation, Equivalent Comparison, Gender